Beef cattle commercial feedlot studies Trial 2--effects on steer performance of variable protein levels, implanting and worming - Harrison, K.F.; Good, D.L.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
A 189-day trial used 280 mixed-breed steers to study effects of various protein levels in finishing steer rations. Rations containing 15.4 or 13.4% crude protein significantly improved rate of gain during the first 42 days compared with an 11.4% crude protein ration. Rates of gain after 91 or 189 days did not differ significantly indicating that steers make compensatory gains. Removing supplemental protein from the ration of 140 steers the final 28 days did not adversely affect rate or efficiency of gain. One hundred forty steers implanted with 36 mg. zeranol and 140 with 36 mg. stilbestrol gained similarly, however, Ralgro implanted steers graded significantly higher. Steers wormed with levamisole or thiabendazole gained 0.06 pound per day faster than steers not wormed.
Keywords: Beef; Rate of gain; Protein; Implant